Metode Pembelajaran Blended Learning Untuk Meningkatkan Motivasi Belajar - Chintya Pradilla Putri; Muhammad Irwan Padli Nasution (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
Web-Based Database in Online Learning: BLENDED LEARNING to Increase Learning Motivation. The current article presents some of the findings of journal-style research focusing on blended learning methodologies. Using data from online journal databases, the results of research journals are analyzed. The focus of this journal article is on mixed learning methodologies. This article discusses the concept of blended learning, blended learning principles, research methods, data collection techniques, research tools, and data analysis. The results of a survey conducted by several journals show that the blended learning model is a combination of traditional classroom learning and online learning. A serious student must be constantly engaged and able to find learning methods that work for them. Teachers only function as facilitators, mediators, and mentors who create conducive conditions for the development of understanding in the minds of students. Application is applied through all subjects taught, through daily activities and curriculum activities, and not only in the subjects of Islamic Education, Moral Education, and Citizenship Education. This blended learning will strengthen the learning model in educational technology.